The Rule of Law and the Reality of the Judiciary during the Period of Palestinian Political Division - Hamad, Ahmed M A (Crown Academic Publishing (CAP), 2020)
The Palestinian Basic Law of 2003 affirmed in Article (6) of it that the principle of the rule of law shall be the basis of government in Palestine. All governmental powers, agencies, institutions, and individuals shall be subject to the law. To enhance the implementation of this principle and ensure its application. The Palestinian legislator stipulated a set of principles related to public rights and freedoms and the reality of the judiciary. The principle of the rule of law is the most important legal guarantee to protect the rights and fundamental freedoms of individuals, as it constitutes in its essence a major guarantee for the protection of public rights and freedoms and the reality of the judiciary. In addition, the judicial authority is important, and it is a guarantee of respect for human rights and protection of the interests of individuals, and it is the body entrusted with it to ensure the rule of law. The independence of the judiciary is the basis of justice, and the complete independence of the judiciary means that no political or administrative authority is permitted to interfere in any act of the judiciary, nor that judges be subject to anything except their conscience, and they have no authority other than the law. The objective of this paper is, therefore, to examine the manifestations of the absence of the rule of law, the infringement of public rights and freedoms, have formed the most prominent problems facing Palestinian society, and this phenomenon ranged between expansion and decline, after the Palestinian political division, according to the developments of the Palestinian national reconciliation and its implications. After the Hamas government took control of the Gaza Strip, in contrast, the Palestinian President appointed a corresponding government in the West Bank, which resulted to two governments, one in the West Bank and the other in the Gaza Strip, which contributed largely to the absence of the rule of law, and a serious deterioration in achieving the principle of the independence of the judiciary. Moreover, this article has explained the impact of the Palestinian political division over the principle of the rule of law and the independence of the judiciary. In order to achieve the objective of this paper, the socio-legal research using the qualitative approach was engaged. This study found that the Palestinian political division led to the absence of the application of the principle of the rule of law and the independence of the judiciary